Lead babies : breaking the cycle of learning disabilities, declining IQ, ADHD, behavior problems, and autism - Cerazy, Joanna; Cottingham, Sandra (Clearwater, FL : Kunati, 2009)
'Reveals important new information about in utero lead transfer from mother to unborn child and details to help readers lead-proof their homes and protect their children from the beginning of pregnancy through rearing'--Provided by publisher.
Keywords: Lead poisoning in children; Lead poisoning in children -- Prevention; Lead -- Physiological effect